The learning of somatic education in question: investigations of a sensible body-subject in dance - Ugo, Marcela; Geraldi, Silvia (Revista dos Trabalhos de Iniciação Científica da UNICAMP, 2019)
The practical-theoretical research started from a personal study about how the contact with somatic education and its articulations with contemporary dance techniques reverberates in several layers of the body and its actions, trying to understand the improvements, the changes and the routes outlined from knowledge. It was possible to notice that the changes happened, mainly, with respect to the creative state established in the research subject and how this is directly related to the return to the own body as an experience that enables the student's autonomy as subject of knowledge. For the development of the research, interviews were carried out with teacher-artists who work with the teaching of classical ballet from a somatic point of view, individual practical laboratories, records in logbooks and bibliographic review, in addition to constant dialogue with the project advisor. The starting point for the practices was the selection of concepts, notions, procedures and resources found in the statements of the interviewed teachers and in the practical and theoretical experiences experienced by the researcher until the time of the laboratories.